El événement barroco: Lope vs. Góngora - Rodrigo Cacho Casal (Mélanges de la Casa de Velázquez)
This article presents an analysis of the literary innovations of Góngora and Lope and their promotional strategies based on the historical method pioneered by Fernand Braudel, which makes a clear distinction between the study of slow, progressive changes in history (longue durée) and particular events and agents of radical change (événements). In his cultist poems, Góngora appeared as a creative genius producing something new ex nihilo. The dissemination of Soledades in Madrid in 1613 and after had the feel of a genuine poetry of événement and caused an uproar. For his part, Lope de Vega sought to curb the cultist revolution, denying that there was any real novelty to it and denouncing the Gongorian poets’ ignorance of tradition. It was precisely behind that tradition that Lope took shelter in order to limit the revolutionary range of his comedias, seeking to renounce any connection with them and denying that he was their inventor. Both authors sought to promote literary modernity, but to do so they adopted opposite ways and theoretical premises, and that is a fundamental aspect of their aesthetic and personal confrontation.